Evaluation of selected aeronautical school libraries through collection mapping - Alay, Hannah Jemaima T.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
An academic library's main purpose is to support its parent institution. This study aimed to evaluate and compare the collection of selected aeronautical libraries; focusing on their curricular support for the degree programs offered by their parent institution.
Two libraries participated in the study: the Philippine State College of Aeronautics (PhilSCA) Library and Wide Aero School of Aviation (WASA) Library. Quantitative method was used to find the libraries' collection size and growth while collection mapping thru conspectus approach was used to determine the collections' quality. The conspectus approach used by De Castro (2009) in her study of the National Defense College of the Philippines Library's was adopted.
The study found that PhilSCA Library has an existing collection development policy which guides the library in selecting, acquiring and weeding its collection. WASA Library, on the other hand, does not have an existing collection development policy nor a licensed librarian to supervise it. Despite this, WASA Library's support of the aviation courses is adequate.
It is also found that both libraries have a strong collection support of the aviation courses of their respective institutions despite not meeting the standards, given by the Philippine Association of Academic and Research Libraries (PAARL).
However since the Philippine government is envisioning the country to be a leader in providing services in aeronautics in the next 10 years, it is recommended that the Civil Aviation Authority of the Philippines (CAAP) should work hand in hand with the education agencies of the government in providing information needed to better equipped our would-be workforce. Both libraries are recommended to seek alternate means of providing much needed information in the field of science and technology to their students. One alternate means is by forming a consortium of aviation school libraries in the Metro.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Philippine State College of Aeronautics; Wide Aero School Aviation; Collections management